Multiple Dimensions of Strategic Spatial Planning : Local Authorities Navigating between Rationalities in Competitive and Collaborative Settings - Granqvist, K.; Mattila, H.; Mäntysalo, R.; Hirvensalo, A.; Teerikangas, S.; Kalliomäki, H. (Routledge, 2021)
This article scrutinises the role of strategic and communicative rationalities in strategic spatial planning. It contributes to the theoretical discussion on strategic spatial planning, where communicative rationality has usually been taken as a normative standpoint, despite the evident role of strategic rationality in guiding planning on the ground. To develop means for equally recognising the two rationalities, the article introduces an analytical framework in which four strategic orientations are identified by juxtaposing coordination through communicative and strategic rationalities with competitive and collaborative settings of social interaction. Its applicability is illustrated with the example of strategic spatial planning in Turku (Finland).
Keywords: Communicative rationality; collaboration; competition; strategic spatial planning; strategic rationality; fi=Aluetiede|en=Regional Studies|